Teori Double Movement dalam IT (Information Technology) Pendidikan Islam Nusantara: Studi Kasus di Sekolah Qaryah Thayyibah Salatiga - Dwi Oktaria (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2022)
This paper aims to analyze the theory of double movement in Islamic education IT Nusantara. The findings show that IT has a great advantage, namely that it can rule the world if used in a positive way. Knowledge can be obtained quickly, all information is universally accepted in an instant when using IT. The advantages of IT in Islamic education in the archipelago will make it easier for teachers and students in the learning process, but it needs supervision from teachers to students so that students are not trapped in the misuse of IT in education. Teachers should close sites that make students lazy to study. IT in the Al-Quran has been explained that Allah. has given instructions to humans to use their minds to develop the sophistication of today's technology.